Prophetic Education in the Era of Digital Transformation: Constructing a Framework for Character Development Among Muslim Students - Huzaiman Hushin; Yousif Mahmadov; Markhabat Bolat; Mohammad Ahmad Bani Amer (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
This study aims to examine the role of Prophetic Education in the era of digital transformation by constructing a comprehensive framework for character development among Muslim students. The rapid expansion of digital technologies has created both opportunities and ethical challenges that require educational systems to integrate technological competence with moral and spiritual development. The research employs a qualitative library research design through a systematic literature review including peer-reviewed journal articles, books, and policy reports. Data were analyzed using thematic content analysis to identify key concepts related to prophetic education, character formation, digital citizenship, and digital ethics. The findings reveal that prophetic values such as ṣidq (truthfulness), amānah (trustworthiness), ‘adl (justice), raḥmah (compassion), ḥikmah (wisdom), and taqwā (God-consciousness) provide a strong ethical foundation for addressing challenges in digital environments. The study further shows that these values align with contemporary frameworks of character education and digital citizenship, particularly in promoting ethical decision-making, responsible technology use, and social responsibility. The novelty of this study lies in the development of the Prophetic Digital Character Education Framework (PDCEF), an integrative model that synthesizes Islamic prophetic principles with modern educational theories to guide character development in digitally transformed learning environments. The study concludes that prophetic education offers a holistic and transformative approach to cultivating morally grounded and digitally responsible Muslim students.